Interpersonal Violence Victimization Among College-Attending and Non-College-Attending Emerging Adults - Daly, Kelly A.; Heyman, Richard E.; Smith Slep, Amy M.; Lorber, Michael F.; Cantor, David; Fisher, Bonnie S.; Lapshina, Natalia; Chibnall, Susan H.; Townsend, Reanne (Emerging adulthood (Thousand Oaks, CA), 2025)
It is well-established that rates of interpersonal violence (IV; physical and emotional intimate partner violence [IPV], non-consensual sexual contact [NCSC], and stalking) peak at 18–24 years of age. Most emerging-adult IV research has been conducted with college samples, making increased risk for IV in college a widely held, but perhaps unjustified, assumption. This nationally representative study (N = 1025) assessed high school seniors on IV victimization and re-assessed them the spring following college enrollment (n = 779) or non-enrollment (n = 246). Replicating prior research, we found few differences in prevalences of IV among college-attending and non-attending emerging adults. After controlling for demographics and baseline victimization, only clinically significant (impactful) physical IPV victimization differed between groups, with college conveying a protective effect (OR = 38, 95% CI: .15 – .99). Explication of proximal and distal factors that inform risk for IV among emerging adults on different trajectories is essential for improved prevention and response.